The prognostic significance of a positive direct antiglobulin test in chronic lymphocytic leukemia: a beneficial effect of the combination of fludarabine and cyclophosphamide on the incidence of hemolytic anemia - Dearden, Claire; Wade, Rachel; Else, Monica; Richards, Sue; Milligan, Don; Hamblin, Terry; Catovsky, Daniel (Blood, 2008)
Autoimmune hemolytic anemia (AHA) is a common complication in chronic lymphocytic leukemia (CLL). The UK LRF CLL4 trial is the largest prospective trial in CLL to examine the prognostic impact of both a positive direct antiglobulin test (DAT) and AHA. Seven-hundred seventy-seven patients were randomized to receive chlorambucil or fludarabine, alone or with cyclophosphamide (FC). The incidence pretreatment of a positive DAT was 14%. Ten percent developed AHA. The DAT correctly predicted the development, or not, of AHA after therapy in 83% of cases, however only 28% of DAT-positive patients developed AHA. Of 299 patients tested both before and after treatment, those treated with single-agent fludarabine were most likely to remain DAT positive and to change from negative to positive. Patients treated with chlorambucil or fludarabine were more than twice as likely to develop AHA as those receiving FC. In a multivariate analysis, stage C disease and high β2 microglobulin were independent predictors of a positive DAT result. AHA, or a positive DAT, with or without AHA, independently predicted for reduced overall survival (OS). Four deaths, all on fludarabine monotherapy, were attributed to AHA. In conclusion, DAT status at the time of initiation of therapy provides a new prognostic indicator, although FC may protect against AHA. This trial was registered at http://isrctn.org as no. 58585610.